2019
DOI: 10.1071/an17757
|View full text |Cite
|
Sign up to set email alerts
|

Determination of range enrichment for improved hen welfare on commercial fixed-range free-range layer farms

Abstract: An observational study on range enrichment was conducted on three commercial fixed-range, free-range layer farms comprising four flocks in South Australia (flock sizes ranged from 3000 to 11700 hens). Two strategies were compared; a ‘standard’ Control treatment, typical of the type of range used in the commercial industry and a highly ‘enriched’ treatment. Both treatments were implemented on the same range with no subdivisional fences. The highly enriched side of the range incorporated shade shelters, alongsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
3
21
0
2
Order By: Relevance
“…The extent of damage was confounded with range use for the selected hen groups making it difficult to determine the role of feather damage in the levels of fear, and the causative relationship with range use. Previous studies have found better plumage condition in hens scored while outdoors compared to hens scored while indoors (De Koning et al, 2018), better plumage in those hens that ranged farthest (Chielo et al, 2016) or better plumage in hens tracked to range more frequently (Rodriguez-Aurrekoetxea and Estevez, 2016). But not all studies have found associations between ranging and plumage condition (Hartcher et al, 2016;Larsen et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…The extent of damage was confounded with range use for the selected hen groups making it difficult to determine the role of feather damage in the levels of fear, and the causative relationship with range use. Previous studies have found better plumage condition in hens scored while outdoors compared to hens scored while indoors (De Koning et al, 2018), better plumage in those hens that ranged farthest (Chielo et al, 2016) or better plumage in hens tracked to range more frequently (Rodriguez-Aurrekoetxea and Estevez, 2016). But not all studies have found associations between ranging and plumage condition (Hartcher et al, 2016;Larsen et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…The hens that ranged the most showed the best plumage coverage which provides further support to previous research. Several studies have demonstrated better plumage in individuals, or flocks that show more frequent use of the outdoor range (De Koning et al, 2018;Lambton et al, 2010;Mahboub et al, 2004;Rodriguez-Aurrekoetxea & Estevez, 2016), or who range farthest when outdoors (Chielo et al, 2016). It might be that hens outdoors are able to or are motivated to engage in more foraging compared with hens indoors (Campbell et al, 2017) where a lack of foraging is often redirected to feather pecking, causing plumage damage (Bestman et al, 2009;Gilani et al, 2013;Rodenburg et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Individually tracked free-range hens that use the outdoor area more, show less feather damage than hens that prefer to spend time indoors (Mahboub et al, 2004;Rodriguez-Aurrekoetxea & Estevez, 2016). Similarly, opportunistic scoring of hens on the range has shown better plumage condition compared with hens scored in the shed (De Koning et al, 2018) and better plumage in hens that ranged farther (Chielo et al, 2016). Outdoor ranging hens or hens that have access to a range area show comparatively reduced footpad dermatitis (Heerkens et al, 2016;Rodriguez-Aurrekoetxea & Estevez, 2016) and range use keeps toenails shortened (Campbell et al, 2017;Yilmaz Dikmen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…occurred on those days. Observations took place at eight times during production when the hens were 30,34,38,42,46,50,54, and 58 weeks of age (LW).…”
Section: Behavioral Observationsmentioning
confidence: 99%
“…Many studies have shown that feather pecking and cannibalism are influenced by various factors (e.g., genetics, group size, diet composition or structure, and light regimens) [16][17][18][19][20][21]. The provision of suitable litter [22][23][24][25][26] and enrichment material [27][28][29][30][31][32][33][34] has been found to reduce feather pecking and cannibalism. Red jungle fowl are known to spend a large proportion of their daytime activity on ground scratching (60%) and pecking (34%) on forest soil (i.e., foraging) [35].…”
Section: Introductionmentioning
confidence: 99%